TELBIVUDINE IN THE TREATMENT OF HEPATITIS B VIRUS REACTIVATION IN CANCER PATIENTS RECEIVING CHEMOTHERAPY - Manzoor Ahmad Wani; Jaswinder Singh Sodhi; Showkat Ali Zargar; Gul Javid; Sheikh Aijaz Aziz; Ghulam Nabi Yattoo; Altaf Shah; GM Gulzar (Medico Research Chronicles, 2018)
Background & Aims: Hepatitis B virus Reactivation (HBVR) in cancer patients receiving chemotherapy is potentially fatal condition and needs prompt diagnosis and treatment. Treatment of such patients has been attempted with lamivudine, entecavir, and tenofovir with variable success rates. Although a rapidly acting highly potent antiviral, telbivudine has not been studied in HBVR and our aim was to study the efficacy of telbivudine in such patients. Methods: This prospective study of four patients with HBVR who were suffering from different malignancies was conducted in a tertiary care center. These patients were referred with transaminitis and on investigating proved to be having HBVR. After starting them on Telbivudine 600mg OD, these patients were followed very closely on OPD basis. Results: 3 out of 4 patients developed HBsAg seroconversion and the drug could be stopped within 1 year of treatment in all three of them. In one patient, HBe seroconversion was achieved. Conclusions: Telbivudine is an effective alternative to entecavir and tenofovir in cancer patients with HBVR.